Regulatory Effect of Melatonin on Cytokine Disturbances in the Pristane-Induced Lupus Mice - Ling-ling Zhou; Wei Wei; Jun-feng Si; Dong-ping Yuan (Mediators of Inflammation)
Systemic lupus erythematosus (SLE) develops in relation to many environmental factors. In our opinion, it is more important to investigate the effect of melatonin on the environmental- related SLE. In the present study, 0.5 ml pristane were used to induce SLE in female BALB/c mice. Melatonin (0.01, 0.1, 1.0 mg/kg) was orally administered immediately after pristane-injection for 24 weeks. IgM anti ssDNA and histone antibodies were detected after 0, 1, 2, 4, 8 weeks pristane injection. The levels of IL-2, IL-6 and IL-13 were detected after 24 weeks. Renal lesions were also observed. The results showed that melatonin antagonized the increasing levels of IgM anti ssDNA and histone autoantibodies. Melatonin could also decrease the IL-6 and IL-13 production and increase the IL-2 production. Besides, melatonin could lessen the renal lesions caused by pristane. These results suggested that melatonin has a beneficial effect on pristane-induced lupus through regulating the cytokines disturbances.